2006
DOI: 10.1016/j.athoracsur.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-Related Differences in Ischemia/Reperfusion Injury and Cardioprotection: Effects of Diazoxide

Abstract: Background-Recent studies have demonstrated that aging is associated with reduced tolerance to ischemia and that the aged (not senescent) female heart has greater susceptibility to ischemia as compared with the aged male heart. Previously, we have shown that ischemia can be modulated with cardioplegia in the male heart; however, efficacy in the female heart was unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 26 publications
9
65
0
Order By: Relevance
“…We also demonstrated that the effects of global ischemia were partially ameliorated by cardioplegia ± diazoxide, but this cardioprotection was significantly decreased in the aged compared with the mature heart and significantly decreased in the aged female compared with the aged male rabbit heart [2]. These animal studies are consistent with human studies indicating that women have a significantly greater risk potential compared with men and worse outcomes after cardiac surgery [3,4].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…We also demonstrated that the effects of global ischemia were partially ameliorated by cardioplegia ± diazoxide, but this cardioprotection was significantly decreased in the aged compared with the mature heart and significantly decreased in the aged female compared with the aged male rabbit heart [2]. These animal studies are consistent with human studies indicating that women have a significantly greater risk potential compared with men and worse outcomes after cardiac surgery [3,4].…”
supporting
confidence: 80%
“…All rabbits were anesthetized with pentobarbital sodium (Nembutal, 100 mg/kg; Abbott Laboratories, North Chicago, IL), and heparin (200 U/kg) was given intravenously through the marginal ear vein [1,2,10]. Langendorff perfusion was performed as previously described [1,2,10].…”
Section: Langendorff Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the use of organs from older donors is a major concern in transplantation, our approaches aiming to determine more effective and secure myocardial preservation solutions for older donors will advance transplantation medicine and could have substantial clinical impact. We and others have shown that aging is related to reduced tolerance to myocardial ischemia and postischemic functional recovery and infarct size is affected by age [25]. Hearts from older donors are associated with increased myocardial stunning, decreased recovery of hemodynamic and high-energy phosphates, and greater overall tissue damage after ischemic insult [26].…”
Section: Commentmentioning
confidence: 96%
“…Ovariectomy also negates cardioprotection in an I/R model of injury, and exogenous E2 treatment can restore protection (23). However, there are some studies that show no benefit of E2 in I/R injury (24,25). The discrepancies in protection could be due to species differences (rat versus dog and rabbit) or differences in estrogen treatment or cycle stage.…”
Section: Estrogen and Sex Differences In Cardiovascular Diseasementioning
confidence: 97%